(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
This study thematically examines the term ra’fah in the Qur’an, particularly in the context of implementing zina (adultery) sanctions, aiming to formulate a conceptual reconciliation between the divine mercy and the principle of justice in Islamic law. The background of this research is based on the common practice in society of resolving zina cases through mediation or customary law, which contradicts the provisions of Islamic criminal law as stipulated in Q.S. An-Nur verse 2 and Aceh Qanun No. 9 of 2008, as well as the phenomenon of victims marrying their abusers to preserve family honor, which obscures the protection of victims’ rights and justice. This study employs a qualitative method with a thematic interpretation approach to Qur’anic verses containing the term ra’fah. The findings reveal that ra’fah is explicitly mentioned only in two verses, Q.S. An-Nur verse 2 and Q.S. Al-Hadid verse 27, both revealed in Medina; in Q.S. An-Nur verse 2, ra’fah means the prohibition of allowing compassion to prevent the enforcement of zina sanctions in order to uphold justice and legal certainty, while in Q.S. Al-Hadid verse 27, ra’fah is associated with gentleness and compassion instilled in the hearts of the followers of Prophet Isa (Jesus). These findings affirm that ra’fah is not an obstacle to law enforcement but an ethical foundation that balances divine mercy and legal firmness in the implementation of Islamic sharia. The study recommends a comprehensive understanding of ra’fah as an ethical basis for enforcing Islamic criminal law to create harmony between compassion and justice. The novelty of this research lies in its focused thematic analysis of ra’fah in the context of zina sanctions, which has been rarely explored, and the affirmation that ra’fah is an ethical principle guiding law enforcement to remain humane without compromising firmness, thus contributing new theoretical insights to the development of Islamic law, especially in the enforcement of hudud sanctions through a more comprehensive and contextual interpretation of ra’fah.